The novel ageing-induced long non-coding RNA MIRIAL controls endothelial cell and mitochondrial function. (3rd October 2022) - Kohnle, C; Theodorou, K; Koziarek, S; Sommer, J; Busscher, D; Wagner, J U G; Wittig, I; Dimmeler, S; Boon, R A
Abstract:  : Vascular ageing is a key risk factor for cardiovascular diseases and is characterised by a continuous decline in endothelial cell function. Despite progress in recent years, the molecular mechanisms for this deterioration remain incompletely understood. Long non-coding RNAs (lncRNAs) are a heterogeneous class of RNAs that have been shown to regulate gene expression and protein function, however, little is known about their role in the ageing-associated dysregulation of endothelial cell (EC) function. In this study, we aimed to identify and functionally characterise a novel ageing-regulated lncRNA in ECs. Using RNA sequencing data of cardiac ECs derived from 12 weeks young and 20 months old mice, we identified Mirial as an ageing-induced lncRNA (1.32-fold, p=0.00005). Mirial is conserved between mice and humans and has no obvious coding potential. GapmeR-mediated silencing of MIRIAL in human umbilical vein ECs (HUVECs) decreased cell proliferation by 50%, migration by 24% (p=0.045) and basal angiogenic sprouting by 53% (p=0.0029), without affecting apoptosis or senescence. Additionally, silencing of MIRIAL increases mitochondrial mass (1.8-fold, p<0.01) and spare respiratory capacity (1.95-fold). Preliminary data from the hearts of Mirial knockout mice confirm the elevated mitochondrial mass after Mirial ablation (1.26-fold, p=0.05). In HUVECS, MIRIAL is mainly associated with the chromatin (80%), suggesting a role in the regulation of gene expression. Pathway analysis showed an overrepresentation of p53 target genes that were upregulated upon MIRIAL knockdown, which was validated using qRT-PCR (1.8–5.2-fold increases). Interestingly, this effect is fully dependent on the presence of p53. Moreover, p53 and phospho-p53 (Ser15) were both increased (1.8-fold, p=0.01 and 2.9-fold, p=0.02, respectively) after MIRIAL silencing. Pulldown of MIRIAL identified DDX5 and MRPL41 as direct p53 interactors and RNA immunoprecipitation revealed that MIRIAL physically interacts with p53 (3.75-fold enrichment, p<0.01). Gene set enrichment analysis of RNA sequencing data revealed that 10% of deregulated genes after MIRIAL knockdown have a binding site for Forkhead Box O (FoxO) transcription factors. In particular, FoxO1 is known as one of the key players in endothelial proliferation and regulation of angiogenesis as well as in mitochondrial biogenesis. Taken together, MIRIAL is an ageing-induced lncRNA in endothelial cells acting as a key regulator of metabolic and cellular function. MIRIAL promotes cell proliferation, migration and basal angiogenic sprouting while decreasing mitochondrial function. We hypothesise that MIRIAL influences these cellular functions by affecting the p53 pathway and mitochondrial respiration through FoxO signalling. The results from the present study suggest that modulation of cellular MIRIAL expression may be a promising strategy to prevent or even reverse ageing-induced functional decline of ECs, both in vitro and in vivo. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Deutsche Forschungsgemeinschaft - Collaborative Research Centre (SFB) 834 - Project B9Deutsche Forschungsgemeinschaft - Collaborative Research Centre/Transregio (TRR) 267 - Project B4